Are Profit and Profitability the Same Thing? - Edward Evans (EDIS)
The terms “profit” and “profitability” are used quite frequently in everyday talk to mean the same thing. We often hear someone say “my business made a profit last year” or “my business was profitable.” But are the two statements equivalent? In this article, I’ll explain the two terms, outlining the difference between them, and discussing a few things that growers can do to improve the profitability of a farm business. This 4-page fact sheet was written by Edward Evans and published by the UF Department of Food and Resource Economics, February 2014.